Pitting Corrosion of Tin in Halogen Ions-Inhibition Using Organic Carboxylates - El-Kot, A.M.; Abd El-Aal, A.; Ghuzza, A. (Asian Journal of Chemistry, 2010)
A systematic study of the pitting corrosion on tin metal by halogen ions Cl–, Br– and I– was carried out in sodium carbonate solutions. The strongest depassivating effect of Cl– ions than Br– and I– ions was ascribed to the larger adsorbability of the Cl– ion and thus its forming surface complex species by the overlapping of the chloride ion and the metal orbitals. Also the inhibition of the pitting corrosion of tin electrode using some organic carboxylates has been investigated. The inhibition of tin in 0.05 M Na2CO3 + 0.04 M NaCl increases in the order: formate <acetate <succinate <tartrate <citrate.